2022
DOI: 10.3390/biom12020186
|View full text |Cite
|
Sign up to set email alerts
|

piRNAs and PIWI Proteins as Diagnostic and Prognostic Markers of Genitourinary Cancers

Abstract: piRNAs (PIWI-interacting RNAs) are small non-coding RNAs capable of regulation of transposon and gene expression. piRNAs utilise multiple mechanisms to affect gene expression, which makes them potentially more powerful regulators than microRNAs. The mechanisms by which piRNAs regulate transposon and gene expression include DNA methylation, histone modifications, and mRNA degradation. Genitourinary cancers (GC) are a large group of neoplasms that differ by their incidence, clinical course, biology, and prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 208 publications
(205 reference statements)
0
18
0
Order By: Relevance
“…RNAPol II is responsible for producing long single-stranded RNA precursors which are matured into fragments of 25–40 nt by the endonuclease MitoPLD/Zucchini (Zuc). The final length of the mature piRNA depends on the target PIWI proteins to which the piRNA binds [ 38 , 62 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAPol II is responsible for producing long single-stranded RNA precursors which are matured into fragments of 25–40 nt by the endonuclease MitoPLD/Zucchini (Zuc). The final length of the mature piRNA depends on the target PIWI proteins to which the piRNA binds [ 38 , 62 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…The wide range of ways by which piRNAs can regulate gene expression suggests that these piRNAs are more powerful regulators than the better-known miRNAs. The mechanisms of action of these ncRNAs require the association of ncRNA to the PIWI proteins to suppress expression of transposable elements, and their transcription could be regulated by DNA methylation or histone modification [ 62 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…The biogenesis and role of piRNA in several cancer localizations at once have been studied ( Guo et al, 2020 ). A number of studies suggest that piRNAs are involved in oncogenesis through their influence on genes, but how this occurs remains unknown ( Fonseca et al, 2020 ; Wang et al, 2022a ; Zhang et al, 2022a ; Zhang et al, 2022b ; Cai et al, 2022 ; Zhang et al, 2022c ; Hanusek et al, 2022 ). In recent years, the study of piRNAs has continued to receive a great deal of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that other proteins could be used as markers for their diagnostic and prognostic values, including P-element-induced wimpy testis (PIWI) proteins (Jiang et al, 2021;Hanusek et al, 2022). Some of these biomarkers have been proposed as potential, accurate, simple and noninvasive biomarkers for early detection of HCC.…”
Section: Introductionmentioning
confidence: 99%